Spatial Market Integration of Shallot in Indonesia - Astuti Rahmawati; Anna Fariyanti; Amzul Rifin (School of Business, Bogor Agricultural University (SB-IPB), 2018)
Shallot is a horticultural commodity which has high economic and strategic values. Unbalanced supply and demand of shallot each province in Indonesia cause trade flows from surplus areas to deficit areas and indicate there is a market integration. This research aimed to analyze spatial market integration of shallot at the producer level in Indonesia. Methods of this research used included Johansen Co-integration, Granger Causality, and Error Correction Model. Results of this research exhibit that there is no complete spatial market integration among shallot producer markets. There are approximately 40 co-integrated pairs of producer markets (44.944%), and the rest of 49 (55.056%) pairs of producer markets are not co-integrated. Based on the causality test, the producer markets such as Central Java, East Java, and West Nusa Tenggara are price-leading markets. Approximately 74 pairs (83,146%) of producer markets are integrated into the short run. Government policy that can be implemented to control price fluctuations at producer level is fairly floor price policy specifically made for three price-leading markets. To improve spatial market integration of shallot in Indonesia, the government needs to make policies such as upgrading quality of physical infrastructure (length of paved roads) and educating human capital (producers) to access market information technology.Keywords: producer market, shallot, spatial market integration, Johansen Co-integration, Granger Causality